ANALISIS PERBEDAAN PERATURAN DAFTAR NEGATIF INVESTASI DAN DAMPAKNYA PADA POLITIK HUKUM INVESTASI DI INDONESIA - Salsabila, Sofha; Allagan, Tiurma Mangihut Pitta (JURNAL DARMA AGUNG, 2023)
The Investment Negative List (DNI) regulations are a vital instrument in regulating foreign and domestic investments in Indonesia. This article discusses the significant changes that have occurred in the DNI regulations over time and how these changes have influenced the framework of Indonesia's investment policies. This research conducts an in-depth analysis of the differences in the Investment Negative List (DNI) regulations applied in various periods in Indonesia and their impact on investment law and policy. The research methodology will use normative juridicial research that involves the analysis of DNI regulation documents, investment policies, and relevant literature. The results of the analysis reveal that changes in the DNI regulations reflect a shift in Indonesia's investment law and policy perspective, moving from a more restrictive approach to a more open stance towards investment.